The Role Of Cinema In The System Of Education (Eurasian Scientific Herald, 2022)
Film works are an excellent means of developing the senses. Therefore, the educational role of cinema is greater than it might seem, when the expediency of using pictures is judged only by their subject matter. So, the moral education of young people is promoted not only by tapes, about which it is customary to say that they are devoted to ethical problems. Any talented film develops the emotional apparatus of the young viewer. If the picture is about modernity, it also prepares boys and girls for the system of relations that is characteristic of our society, partially includes them in these relations.